Proceso de atención de enfermería en neonato de 4 días con Ictiosis Arlequín - Carbo Caamaño, Carlos Ariel (2021)
Harlequin ichthyosis is defined as a genetic disorder of autosomal recessive inheritance, which severely affects the ABCA12 gene. Which is responsible for the coding of an essential protein, for the maintenance of the skin's lipid barrier. However, this pathology is diagnosed with the naked eye due to its patchy appearance of the skin, due to the multiple hyperkeratosis plaques that present fissures (Almendraa & Aranibar, 2017). We must know that the association of other malformations is very frequent, such as; ectropion (eversion of the eyelids), eclabium (everted lips), and hypoplasia of nasal bones, pinnae, and fingers and toes. Therefore, harlequin ichthyosis is the most severe and aggressive form of congenital ichthyosis, which has a low prevalence of approximately 1 / 300,000 births with variable clinical expression, an unfavorable evolution and a reserved prognosis (WHO / PAHO, 2017). Prenatal diagnosis is possible in some ichthyosis and should be evaluated when there is a family history with a genetic pattern that makes transmission possible. The most commonly used techniques may include amniocentesis, villus biopsy, fetal skin biopsy, blood and urine analytical studies (Ávila, Montoya, & Bustillo, 2016). The initial management of these patients includes good and correct hygiene, humid heat in an incubator, high fluid intake to avoid dehydration due to transepidermal losses, and emulsifying ointments. Finally, our patient was also administered empirical antibiotic therapy and morphine intravenously in infusion, prior to transfer to the neonatal intensive care unit, the Nursing Care Process was drawn up in a 4-day neonate with Harlequin Ichthyosis with the objective to restore their state of health through physical assessment and functional patterns. Using the Marjory Gordon model to prioritize nursing interventions and develop a specific care plan based on the needs required by the patient.